Pivoting the seesaw? Negotiating the tensions of balancing ethical and methodological considerations in designing research that involves children and young people. Issue 1 (2nd January 2020) - Kay, Lynda
ABSTRACT: CYP fall within the range of groups classified as vulnerable. The aligning of vulnerable with notions of incompetence, risk of harm and poor skills and abilities elicits a heightening of tensions surrounding perception of risk to CYP regarding their involvement in research. This paper explores the factors related to ethical principles and methodological choices that must be balanced by researchers throughout the research process for research involving CYP and other vulnerable participants. The decision-making processes in relation to ethical and methodological considerations throughout the design and implementation of the research are likened within this article to balancing a seesaw. A framework, containing prompts and questions, to support reflexive ethical decision-making is proposed to support researchers with balancing the seesaw to protect CYP and to facilitate opportunities for them to articulate their views and experiences. This paper contributes to the debates surrounding the involvement of CYP in research and adds support to greater weighting towards ethics, upon the pivot of the seesaw of decision making in research design.